The evolution of cooperation in strategic alliances: Initial conditions or learning processes? - Doz, Yves L. (Strategic Management Journal, 2007)
We examine how the learning, along several dimensions (environment, task, process, skills, goals), that takes place in strategic alliances between firms mediates between the initial conditions and the outcomes of these alliances. Through a longitudinal case study of two projects in one alliance, replicated and extended in another four projects in two alliances, a framework was developed to analyze the evolution of cooperation in strategic alliances. Successful alliance projects were highly evolutionary and went through a sequence of interactive cycles of learning, reevaluation and readjustment. Failing projects, conversely, were highly inertial, with little learning, or divergent learning between cognitive understanding and behavioral adjustment, or frustrated expectations. Although strategic alliances may be a special case of organizational learning, we believe analyzing the evolution of strategic alliances helps transcend too simple depictions of inertia and adaptation, in particular by suggesting that initial conditions may lead to a stable ‘imprinting’ of fixed processes that make alliances highly inertial or to generative and evolutionary processes that make them highly adaptive, depending on how they are set.